Markobar: Telaah Adat dan Pandangan Islam - Nasution, Abdul Gani Jamora; Harahap, M. Abrar Putra Kaya; Ramadhani, Fitri; Azahra, Zelma; Siregar, Amanda Fhadillah (Lembaga Yasin AlSys, 2023)
The purpose of this research is to find out how the Markobar Tradition is carried out and also to find out how Islam views the Markobar Tradition of the Mandailing tribe. The method used in this research is a qualitative method with a descriptive approach. Data collection techniques are carried out by means of observation, interviews, and documentation. The research results obtained are that Markobar is one of the customs of the Mandailing tribe in the form of oral literature. Generally, markobar is carried out during Siriaon events (a party in a happy atmosphere) or a party in an atmosphere of mourning (Silulutun). In carrying out the traditional Markobar wedding event, it was opened by the Suhut. Then answered by Mora to Kahanggi and continued with advice by the families of the bride and groom based on the Dalian Natolu system. At the death ceremony, Markobar was only different from advising him, the messages conveyed were encouragement and condolences. The activity was opened Suhut and continued by the family. All kinds of cultural values that are in line with Islamic teachings may be carried out by looking at the Shari'a and the provisions of Allah SWT. Markobar practices are in line with Islam, namely giving advice to do good and leave bad, but there needs to be a little clarification in the procedure for implementing it, namely to pay more attention to time and to always remember Allah SWT.